CORRELATION ANALYSIS OF SOIL CHARACTERISTICS AND SOIL QUALITY INDEX TO THE ESTIMATION OF CO2 ABSORPTION IN PLANTS IN HALIM PERDANA KUSUMA URBAN FOREST, EAST JAKARTA - CLAUDIA ELVIRA SUBAN (NIM : 11513051), NADINE
Along with the advent of activities and development of DKI Jakarta as a capital city, the need for urban forests as a provider of ecosystem services is increasing. Urban forest has many functions, among others, as an absorber of CO2 that generated by urban activities. In improving the functions of urban forest, it is necessary knowledge about the characteristics and quality of growing media of plants. The information is used to improve the physiological function of plants in absorbing CO2. This study aims to determine the nature and soil quality index (SQI) against the estimated amount of CO2 absorption in plants and the determination of optimum land cover types based on SQI in increasing the amount of CO2 uptake in plants in Halim Perdana Kusuma Urban Forest. Research conducted through plot selection with purposive sampling method, plot preparation, vegetation analysis, soil sampling and testing, calculation of CO2 absorption in plants, calculation of SQI, and correlation analysis of soil characteristics and SQI to amount of CO2 absorption by plants. The plot consists of 8 vegetated plots; 3 open land plots (LA) (no vegetation), 3 half-open land plots (LS) (plants), and 3 closed land plots (LT) (trees and plants). Based on the results of the research, the estimated number of CO2 absorption in plants is 1924.334 ton per ha (1902,504 ton per ha absorbed by trees and 21,83 ton per ha by plants & litters. The results of correlation test of each variable of soil characteristics and SQI with the amount of CO2 absorption in plants, showed that C-org (-0.094), N (-0.198), P (-0.485), Mg (-0.193), CEC (-0.285), the weight of content (0.116) and porosity (0.116) has a low correlation; pH (0.405), C / N (0.485), Na (0.577), and Kb (0.424) had a fairly low correlation; K-available (-0.621), Ca (0,557), K-total (-0,602), and SQI (0,604) have high correlation. Based on the calculation of the number of IKT through principal components analysis (PCA) and mini data set (MDS), the overall average of SQI is 0.706 (good) and the SQI of LA, LS, LT land cover types sequentially are 0.033 (very low), 0.728 (good), and 0.839 (very good). So, it can be concluded that the soil indicators those affect the amount of CO2 uptake in plants are K-available, Ca, K-total, SQI, and optimum land cover type based on SQI to increase the amount of CO2 absorption in plants is closed land (LT).